ADCK4-Associated glomerulopathy causes Adolescence-Onset FSGS - Kahraman, Emine; Lipska-Ziętkiewicz, Beata S.; Boyer, Olivia; Gribouval, Olivier; Fourrage, Cecile; Tabatabaeifar, Mansoureh; Schnaidt, Sven; Gucer, Safak; Kaymaz, Figen; Arici, Mustafa; Dinckan, Ayhan; Mir, Sevgi; et al. (Journal of the American Society of Nephrology, 2016)
Hereditary defects of coenzyme Q10 biosynthesis cause steroid-resistant nephrotic syndrome (SRNS) as part of multiorgan involvement but may also contribute to isolated SRNS. Here, we report 26 patients from 12 families with recessive mutations in ADCK4. Mutation detection rate was 1.9% among 534 consecutively screened cases. Patients with ADCK4 mutations showed a largely renal-limited phenotype, with three subjects exhibiting occasional seizures, one subject exhibiting mild mental retardation, and one subject exhibiting retinitis pigmentosa. ADCK4 nephropathy presented during adolescence (median age, 14.1 years) with nephrotic-range proteinuria in 44% of patients and advanced CKD in 46% of patients at time of diagnosis. Renal biopsy specimens uniformly showed FSGS. Whereas 47% and 36% of patients with mutations in WT1 and NPHS2, respectively, progressed to ESRD before 10 years of age, ESRD occurred almost exclusively in the second decade of life in ADCK4 nephropathy. However, CKD progressed much faster during adolescence in ADCK4 than in WT1 and NPHS2 nephropathy, resulting in similar cumulative ESRD rates (>85% for each disorder) in the third decade of life. In conclusion, ADCK4-related glomerulopathy is an important novel differential diagnosis in adolescents with SRNS/FSGS and/or CKD of unknown origin.
Gesehen am 18.05.2020
Published online December 31, 2015